Curriculum of Embedded System for Software Colleges - Hongxing, Wei; Tianmiao, Wang (2006 2nd IEEE/ASME International Conference on Mechatronics and Embedded Systems and Applications, 2006)
Embedded system has already been applied in numerous fields, such as the industry control system, information appliances, communication equipments, medical instruments, intelligence instruments and so on. As processors become more powerful, electronic products become more complex. Embedded system designers are able to include design features traditionally associated with personal computer (PC) including graphical user interfaces, TCP/IP networking, and database management. For introducing knowledge of embedded system to student of Master of Software Engineering (MSE), the Software College at Tsinghua University and Beihang University had an opportunity to add technical electives for embedded system, the author received approval to teach embedded system design course. This paper describes the development and implementation of that course toward the goal of teaching students the hardware considerations, software considerations, and design processes involved in embedded system design. In the end, the teaching effect of course for embedded system design is analyzed